Porosity in oxides on zirconium fuel cladding alloys, and its importance in controlling oxidation rates - Ni, N; Lozano-Perez, S; Jenkins, M; Smith, G; Sykes, J; Grovenor, C; English, C (2010)
Much work has been carried out over the past 40 years on the oxidation of zirconium alloys used for nuclear fuel cladding, but there is no consensus as to the critical factors that control kinetics, even though this is vital for the design of materials for higher burn-up regimes. One unanswered question is the role of porosity in controlling oxidation. Here we show that the nature of the nanoscale porosity can be correlated to different stages of the oxidation process. © 2009 Acta Materialia Inc.